Comparative Analysis of Oxidative Stress Markers in Smokers and Non-Smokers with Oral Submucous Fibrosis (Bangladesh Journal of Medical Science, 2026)
Background Oral submucous fibrosis (OSMF) is a chronic, insidious, potentially malignant disorder characterized by juxta-epithelial inflammatory reaction and progressive fibrosis of the lamina propria. Its pathogenesis is multifactorial, with oxidative stress playing a pivotal role. Tobacco smoking, a known independent source of reactive oxygen species, may exacerbate this oxidative burden. Methods: A cross-sectional study was conducted on 100 participants, divided into four groups: Group A (OSMF smokers, n=25), Group B (OSMF non-smokers, n=25), Group C (healthy smokers, n=25), and Group D (healthy non-smokers, n=25). Clinical staging of OSMF was performed. Serum levels of MDA, SOD, GSH, and vitamin C were estimated using standard biochemical assays. Results Group A exhibited the highest mean MDA level (6.18 ± 1.32 nmol/mL), significantly higher than Group B (4.82 ± 1.15 nmol/ mL, p < 0.001), Group C (3.48 ± 0.81 nmol/mL, p < 0.001), and Group D (2.09 ± 0.52 nmol/mL, p < 0.001). Conversely, antioxidant levels were lowest in Group A (SOD: 1.85 ± 0.48 U/mL; GSH: 3.21 ± 0.88 mg/dL; Vit C: 0.72 ± 0.25 mg/dL) and progressively increased through Groups B, C, and D. Within the OSMF cohort (A+B), a significant positive correlation was found between MDA levels and clinical stage of OSMF (r = 0.71, p < 0.001), while SOD, GSH, and vitamin C showed a significant negative correlation. Conclusion The study demonstrates that smoking significantly exacerbates oxidative stress in patients with OSMF, as evidenced by higher MDA and depleted antioxidant levels compared to non-smokers with OSMF. This heightened oxidative state may contribute to accelerated disease progression and increased malignant transformation risk, underscoring the critical importance of smoking cessation in the management of OSMF.Bangladesh Journal of Medical Science Vol. 25. Supplementary Issue 2026, Page : S102-S107